Why Study on a MOOC? The Motives of Students and Professionals - Milligan, Colin; Littlejohn, Allison (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2017)
Massive Open Online Courses have emerged as a popular mechanism for independent learners to acquire new knowledge and skills; however, the challenge of learning online without dedicated tutor support requires learners to self-motivate. This study explores the primary motivations reported by participants in two MOOCs: Fundamentals of Clinical Trials and Introduction to Data Science (n=970). Each MOOC drew a diverse cohort of participants ranging from professionals working in the field to students preparing to enter it. Across both MOOCs, a similar profile of primary motivations emerged, with respondents identifying the potential benefits to their current role, or future career, alongside more general responses reflecting casual interest in the topic or a simple desire to learn. Professionals were primarily motivated by current needs, describing how the course could fill gaps in their formal knowledge, broaden their skillset to increase their effectiveness at work, or enable them to innovate. Professionals also saw the benefit of MOOC study in preparing them for new roles and career progression. Students, meanwhile, used MOOC study to complement their other learning. It is clear that MOOC study represents a popular mechanism for professionals to address both current and future learning needs.